Studies on management of powdery mildew in coriander using new generation fungicides - Nakkeeran, C Ushamalini, S (Journal of Spices and Aromatic Crops, 2017)
Coriander is an important spice crop, affected by powdery mildew caused by Erysiphe polygoni. The present study was conducted to test the efficacy of new generation fungicides i.e., azole compounds for the management of powdery mildew in coriander. Two sprays of propiconazole (0.15%) at 15 days interval i.e. on 30 and 45 days after sowing (DAS) were found to be effective in reducing powdery mildew incidence, which also recorded the highest seed yield.